2012
DOI: 10.1021/la205127x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Properties of Polymeric Aziridine- and Biguanide-Modified Core–Shell Magnetic Nanoparticles

Abstract: Polycationic superparamagnetic nanoparticles (∼150-250 nm) were evaluated as virucidal agents. The particles possess a core-shell structure, with cores consisting of magnetite clusters and shells of functional silica covalently bound to poly(hexamethylene biguanide) (PHMBG), polyethyleneimine (PEI), or PEI terminated with aziridine moieties. Aziridine was conjugated to the PEI shell through cationic ring-opening polymerization. The nanometric core-shell particles functionalized with biguanide or aziridine moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Virucidal molecules cause irreversible viral deactivation, indeed their effect is retained even if dilution occurs after the initial interaction with the virus. 22 There is a vast literature on many virucidal materials ranging from simple detergents, to strong acids, or more refined polymers, 23 and nanoparticles (NPs) [24][25][26][27] that, in some cases, are capable of releasing ions. 28,29 In all cases, the approaches utilized have intrinsic cellular toxicity.…”
mentioning
confidence: 99%
“…Virucidal molecules cause irreversible viral deactivation, indeed their effect is retained even if dilution occurs after the initial interaction with the virus. 22 There is a vast literature on many virucidal materials ranging from simple detergents, to strong acids, or more refined polymers, 23 and nanoparticles (NPs) [24][25][26][27] that, in some cases, are capable of releasing ions. 28,29 In all cases, the approaches utilized have intrinsic cellular toxicity.…”
mentioning
confidence: 99%
“…Modified PEIs were also evaluated by Alvarez-Lorenzo et al synthesizing modified PEI by polymerization of aziridine and magnetite-silica core-shell particles. It was evident that these polymers inhibited bacteriophage MS2, HSV-1, enveloped viral hemorrhagic septicaemia viruses (VHSV), and nonenveloped infectious pancreatic necrosis virus (IPNV) [97]. oxide (Cu2O), sulphide (Cu2S), iodide (CuI), and chloride (CuCl) have high antiviral efficiency, compared to solid-state silver and cupric compounds [22].…”
Section: Amines Containing-polymers and Polycationsmentioning
confidence: 99%
“…This antiviral activity relies on surface modification with sulfonates or other molecules. Bromberg et al (2012) synthesized core-shell silica-magnetic NPs functionalized with poly(hexamethylene biguanide) (PHMBG). The authors reported that NPs exhibited a notable virucidal effect on several virus strains, which occurred via amino alkylation of their genomic materials, blocking genome replication and leading to viral inactivation (Bromberg et al, 2012).…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%